Analisis Prioritas Penyebab Belum Terlaksananya Retensi dan Pemusnahan Dokumen Rekam Medis Rawat Inap di RS Mitra Medika Bondowoso Tahun 2019 - Futari Ayu Istikomah; Novita Nuraini; Feby Erawantini; Efri Tri Ardianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Regulation of health ministry 2018 number 269 on Medical Record stated that the records of medical patient care inpatient in hospital must be kept at least five (5) years on a period since the date of the last patient treated or discharged. Since the Mitra Medika Bondowoso Hospital was found in 2011 the implementation of retention and destruction of medical record documents has never been carried out. This research was aimed to analyze and know the priority cause unimplementation retention and destruction of documents recording the medical -patient hospitalization by USG (Urgency, Seriousness, and Growth) and brainstorming in Mitra Medika Bondowoso Hospital. Type of this research is that qualitative and the technique collection of data by interviews, observation, documentation, and brainstorming. The results were obtained that the priority of the cause unimplementation of retention and destruction of documents medical record that is the double job of the medical record employees, Retention archive schedule in SOPs, and a lack of understanding of the medical record employees with SOP retention and extermination. The improvement efforts for the problems are to add more medical record employees and to build more teamwork between the employees. Another solutions are to make new SOP recently with the addition of the retention archive schedule as well as involving the employees in the preparation of SOPs.